Rebuilding coral reefs: success (and failure) 16 years after low‐cost, low‐tech restoration. Issue 4 (14th March 2019) - Fox, Helen E.; Harris, Jill L.; Darling, Emily S.; Ahmadia, Gabby N.; Estradivari,; Razak, Tries B.
Abstract : Calls for coral reef restoration are increasing amidst continued declines, yet we know little about long‐term outcomes and conditions that lead to successful coral recovery. Here, we report on one of the longest monitoring studies following 16 years of large‐scale, "low‐tech" experimental reef rehabilitation on rubble fields created by chronic blast fishing in Komodo National Park, Indonesia. After blast fishing had stopped, in the absence of rehabilitation, hard coral cover in rubble fields remained about 3% from 1999 to 2016, but on rehabilitation treatments, cover increased from 0% in 2002 to 44.5% (±21.9% SD) in 2016. Coral cover varied among sites and treatments (ranging from <5 to >80% in 2016) in patterns that may reflect current strength and turbidity. Our results demonstrate that low‐tech substrate stabilization can facilitate natural coral recruitment and growth. We conclude that relatively low‐cost methods can deliver sustained rehabilitation of hard coral cover and that long‐term monitoring should be incorporated more widely in restoration activities to inform return on investment.